Goals and Limitations of Modeling Collective Behavior in Biological Systems - Ouellette, Nicholas T.; Gordon, Deborah M. (Frontiers in Physics, 2021)
Local social interactions among individuals in animal groups generate collective behavior, allowing groups to adjust to changing conditions. Historically, scientists from different disciplines have taken different approaches to modeling collective behavior. We describe how each can contribute to the goal of understanding natural systems. Simple models rooted in physics have demonstrated that local interactions far from equilibrium can generate collective states. However, such simple models are not generic and may not fully describe the real biology. Other classes of models that are more akin to engineering descriptions have been proposed for groups where the function of the collective behavior is better understood. However, such models cannot necessarily explain why or how such functions emerge from first principles. We argue that to bring these distinct modeling approaches together, models of collective behavior should be formulated to address specific questions and to allow for validation against real biological systems. As examples, we discuss four forms of collective behavior that differ both in the interactions that produce the collective behavior and in ecological context, and thus require very different modeling frameworks. 1) Harvester ants use local interactions consisting of brief antennal contact, in which one ant assesses the cuticular hydrocarbon profile of another, to regulate foraging activity, which can be modeled as a closed-loop excitable system. 2) Arboreal turtle ants form trail networks in the canopy of the tropical forest, using trail pheromone; one ant detects the volatile chemical that another has recently deposited. The process that maintains and repairs the trail, which can be modeled as a distributed algorithm, is constrained by the physical configuration of the network of vegetation in which they travel. 3) Swarms of midges interact acoustically and non-locally, and can be well described as agents moving in an emergent potential well that is representative of the swarm as a whole rather than individuals. 4) Flocks of jackdaws change their effective interactions depending on ecological context, using topological distance when traveling but metric distance when mobbing. We discuss how different research questions about these systems have led to different modeling approaches.